Effects of different levels of dried onion powder on nutrient digestibility, biochemical parameters, and nitrogen balance in Wistar albino rats with induced hyperuricemia - Umer, Muhammad; Nisa, Mahr Un; Ahmad, Nazir; Rahim, Muhammad Abdul; Al-Asmari, Fahad (Frontiers in Physiology, 2023)
Introduction: Onions (Allium cepa L.) are excellent sources of bioactive compounds and phytochemicals such as allicin, quercetin, fisetin, and other sulfurous compounds. Therefore, our study aimed to investigate the effects of dried onion powder on growth performance, nitrogen balance, and biochemical parameters in Wistar albino rats with induced hyperuricemia. Methods: A total of 24 rats were randomly divided into four groups, with six in each group: HU (positive control) and HOT1, HOT2, and HOT3 groups, which received a diet containing onion powder at concentrations of 11.13, 14.84, and 18.61 g/100 g, respectively. Hyperuricemia was induced in rats by administering a new formulation intraperitoneally (250 mg/kg potassium oxonate) and orally (40 mg/kg potassium bromate) daily for 14 days. After confirmation of hyperuricemia induction, rats were fed with onion-treated diets with various concentrations of quercetin for 21 days. Results: Significant decreases (p ≤ 0.05) in serum uric acid, alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, total bilirubin, total cholesterol, and low-density lipoprotein were observed. An increasing trend (p ≤ 0.05) in the levels of hemoglobin (Hb), white blood cell (WBC), red blood cell (RBC), and platelet count was observed. An improvement in the levels of serum high-density lipoprotein, triglycerides, blood urea nitrogen, serum creatinine, serum total protein and neutrophils, lymphocytes, and monocytes was observed. A positive progress (p ≤ 0.05) was observed in growth performance and nutrient digestibility. Conclusion: In conclusion, a significantly lower uric acid level was observed in rats fed with HOT2 diet. Based on the ratio of the surface area (human/rat), the best recommended dose of onion for the incidence and prevention of hyperuricemia is 189.95 g, corresponding to the dose of 204 mg/day of quercetin in humans.